2015
DOI: 10.1007/s00280-015-2756-1
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel in combination with octreotide shows synergistic apoptotic effect by increasing SSTR2 and SSTR5 expression levels in prostate and breast cancer cell lines

Abstract: These results indicate that this combination treatment is a significant inducer of apoptosis in a synergistic manner in breast and prostate cancer cells. This strong synergism helps to lower the dose of DTX in both types of cancers, thus letting DTX to be used for longer periods by delaying resistance development and lesser side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This study suggests that HDAC inhibitors may have an additional theranostic property in pulmonary carcinoids by increasing SSTR2 expression. As previously reported, there is evidence that the interaction of somatostatin and its’ analogs with somatostatin receptors has an antiproliferative action and can induce apoptosis, in addition to inhibiting tumorigenic hormone and growth factor secretion [8,9]. Furthermore, there is evidence that patients with low tumor SSTR expression have poor prognoses [15,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study suggests that HDAC inhibitors may have an additional theranostic property in pulmonary carcinoids by increasing SSTR2 expression. As previously reported, there is evidence that the interaction of somatostatin and its’ analogs with somatostatin receptors has an antiproliferative action and can induce apoptosis, in addition to inhibiting tumorigenic hormone and growth factor secretion [8,9]. Furthermore, there is evidence that patients with low tumor SSTR expression have poor prognoses [15,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, NET imaging using PET/CT with radiolabeled somatostatin analogs that specifically target somatostatin receptor subtype 2 (SSTR2) is becoming more standard as many NETs overexpress SSTR2 [4,5,6,7]. Indigenously, somatostatin is an anti-cancer neuropeptide, which is associated with the prevention of hormone and growth factor secretions that contribute to tumor growth, inhibition of tumor cell proliferation, and the induction of apoptosis mediated by the five different SST receptor subtypes (SSTR1-5) [8,9]. Clinically used somatostatin analogs have high affinities towards SSTR2, in addition to weaker affinities to SSTR3 and SSTR5 [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, we demonstrated that octreotide suppresses apoptosis in the kidney after HIR. However, octreotide has been noted to induce apoptosis in different cancer cell lines in vitro 26 27 . This discrepancy may be due to different cell types, treatment factors, and experimental conditions etc.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of a similar binding affinity of SSTR2A and SSTR2B the transcription variants differ in their functional outcome, as exclusively SSTR2B putatively suppresses forskolin-stimulated cAMP formation [242]. Treatment of breast cancer cells with a somatostatin analog octreotide in combination with docetaxel was described as an anti-proliferative and apoptosis inducing combination [247]. In primary human somatotroph tumors SSTR2 activation by octreotide at nanomolar concentrations could induce an increased caspase-3 activity [248].…”
Section: Sstr2 As a Novel Therapeutic Targetmentioning
confidence: 99%